Improving strategic learning and self-regulation skills among underrepresented minority students in a summer research education training program - Nishika T. Edwards; Mohammed Khalil; Rich L. Goodwin; Thomas Nathaniel (Frontiers in Education, 2023)
IntroductionThis study examines the effect of educational interventions on strategic learning and self-regulation variables of underrepresented minority students (URMs) who participated in the NIH R25 Research education program.MethodsThe LASSI instrument was administered to 21 URMs who participated in the intervention over 2  years. We collected pre- and post-intervention data before and after the educational intervention.ResultsThere was a significant improvement (p < 0.001) in all strategic learning and self-regulation parameters including attitude, concentration, information processing, motivation, selecting main ideas, self-testing, test strategies, and time management for the pre and post-assessments.ConclusionThe results of this study indicate that self-regulated learning strategies in research education programs are important to help URM’s chances of advancing along scientific and educational pathways.